Salutogenic Education? Movement and Whole Child Health in a Waldorf (Steiner) School. - Sobo, Elisa J. (Medical Anthropology Quarterly, 2015)
Waldorf education, an independent alternative to public schooling, aims to produce holistically healthy graduates in a formulation that rejects the conventional distinction between education and health. Also striving to bridge that divide, this article characterizes the pedagogically salutogenic techniques Waldorf teachers use in pre-kindergarten (pre-K) and lower grade classes and explicates the ethnomedical understandings underlying them. Waldorf teachers position children as budding participants in a unified field of spiritual and other forces, prioritizing whole-child activities that keep these forces healthfully motile. Their work entails a critique not only of mainstream public schooling's ostensibly pathogenic 'head-to-head' focus, but also of the biomedical approach to pediatric health. My analysis of this conjoined critique takes into account the cultural, structural, and existential realities within which Waldorf education's salutary pedagogy is daily framed and fabricated. Further, it explores the implications for anthropology of attending to movement as a key feature of healthful human experience.